Innovative methods of an assessment of physical condition of a person as a factor of ensuring the effective management of a moving object - Самсонкин, Валерий Николаевич; Пугач, Ярославна Игоревна; Друзь, Валерий Анатольевич; Чередниченко, Мария Анатольевна; Шутеев, Вячеслав Вадимович; Шутеева, Татьяна Николаевна; Шишка, Владимир Владимирович; Горина, Виктория Викторовна (Slobozhanskyi Herald of Science and Sport, 2016)
Samsonkin V., Puhach Y., Druz V., Cherednichenko M., Shuteev V., Shutyeyeva T., Shishka V., Gorinа V. Purpose: to establish the basic provisions of influence of a human factor on reliability of functioning of the system "the person – the object of management – the activity environment". Materials and Methods: the general scientific methods of the analysis, analogy, deduction, comparison, statistical information processing. The methods of a statistical control of sample statistics on an alternative sign. The computer data processing with the use of Excel and Turbo Basic. Results: the method of an individual control and an assessment of influence of a human factor on safety of functioning of the system "the person – the object of management – the environment" is developed. Conclusions: the general provisions of the construction of the sign semantic spaces are established, which allow estimating the current functional state of a person–operator during his direct performance of the professional activity that provides control of its sufficient quality.